Libertarianism: For and Against - Machan, Tibor R.; Duncan, Craig (Rowman & Littlefield Publishers, 2005)
Libertarianism: For and Against offers dueling perspectives on the scope of legitimate government. Tibor R. Machan, a well-known political philosopher with libertarian convictions, argues for a minimal government devoted solely to protecting individual rights to life, liberty, and property. Stressing the sovereignty of each individual, Machan argues in favor of limiting democracy's scope and against the redistribution of wealth, or any other sort of taxation. In opposition to libertarianism, philosopher Craig Duncan defends democratic liberalism, which aims to ensure that all citizens have fair access to a life of dignity. This requires measures to protect equality of opportunity, as well as measures to ensure all have access to a decent minimum standard of living. In a dynamic exchange of arguments, critiques, and rebuttals, the two philosophers cut to the heart of this important debate, articulating and defending competing conceptions of such core values as political freedom and equality.